An improved biosensor for acetaldehyde determination using a bienzymatic strategy at poly(neutral red) modified carbon film electrodes - Ghica, Mariana Emilia (2007)
Improved biosensors for acetaldehyde determination have been developed using a bienzymatic strategy, based on a mediator-modified carbon film electrode and co-immobilisation of NADH oxidase and aldehyde dehydrogenase. Modification of the carbon film electrode with poly(neutral red) mediator resulted in a sensitive, low-cost and reliable NADH detector. Immobilisation of the enzymes was performed using encapsulation in a sol-gel matrix or cross-linking with glutaraldehyde. The bienzymatic biosensors were characterized by studying the influence of pH, applied potential and co-factors. The sol-gel and glutaraldehyde biosensors showed a linear response up to 60 [mu]M and 100 [mu]M, respectively, with detection limits of 2.6 [mu]M and 3.3 [mu]M and sensitivities were 1.7 [mu]A mM-1 and 5.6 [mu]A mM-1. The optimised biosensors showed good stability and good selectivity and have been tested for application for the determination of acetaldehyde in natural samples such as wine.